Penerapan Model Pembelajaran Sejarah Lokal sebagai upaya Meningkatkan Motivasi Belajar Siswa : (Penelitian Tindakan Kelas di SMA Negeri 2 Serui Kabupaten Kepulauan Yapen Provinsi Papua) - Bob Maikel Matui (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the application of the local history learning model in increasing student learning motivation. This research is classroom action research. The subjects in the research were 40 class XI IPS 3 students. The data collection technique used in this research uses observation, interviews and documentation. The steps taken in this research are starting with orientation before taking action, plan (planning), act (implementation of action), observe (observation) and reflect (reflection). ). The research results show that the application of the local history learning model can increase students' learning motivation. Meanwhile, in particular, it shows that the application of the environmental exploration model of history learning can increase student learning motivation, increase student activity and creativity in learning. This is proven from cycle to cycle, there is an increase in student activity, including actively asking questions, searching for and processing information, having the courage to express ideas, answering questions asked, developing and analyzing the historical events being studied, exploring learning experiences, applying learning experiences. , exchange ideas about the material with colleagues, be able to work together in groups, and make conclusions. Thus, the environmental exploration approach can be used as a suitable alternative in history learning to increase students' learning motivation both in the form of processes and in the form of products in the form of values.